A Study On The Rate And Pattern Of Cutaneous Reactions To Drugs - Gangopadhyay D.N; Chowdhari S (Wolters Kluwer Medknow Publications, 1995)
A study was undertaken to determine the pattern of cutaneous reaction to drugs during June and July 1994 at the Skin OPD, N.R.S Medical College, Calcutta. Drug rash comprised of 43 patients (about 1%) of total 4,431 patients. There was no age or sex predilection. Exanthematous rash was the commonest type affecting 35% patients, followed by uritcaria including angioedema and FDR, each affecting 23.3% patients. An erosive buccal mucous membrane lesion without skin affection was found in 2 cases. Among the drugs co-trimoxazole was the main offender (37.3%), followed by analgesics (25.6%), ampicillin (9.3%) and A.T. drug (2.3%). Drugs responsible could be elicted in 2 patients and 1 patient gave history of taking medicine. Only one patient gave of Known allergy to some drug.